STUDI KARAKTERISTIK FISIK DAN MEKANIK EDIBLE FILM PATI UBI JALAR UNGU DENGAN PENAMBAHAN KITOSAN - Ekariski, Dhita; Basito, Basito; Yudhistira, Bara (Jurnal Teknologi Hasil Pertanian, 2017)
Edible film is one of alternative packaging which can consume and still protect product from losing nutrition, appearance, flavor, dehydrate and deteriorate at storage and isn’t damage environment. More research using local starch from sweet potato (Ipomea batatas L. poir) was studied. But, characteristic from sweet potato starch shows poor in quality. So, mixing starch with chitosan studied to make characteristic of edible film more useable for wide area. This research to know how is characteristic of edible film starchchitosan. One edible film use 0,8 mL glycerol or 20% (v/w) and chitosan’s soluble 1% acetate acid. One factor uses in this research is amount of chitosan with 3 level 0,5 gram; 1,0 gram; and 1,5 gram. Then, edible film analyzed physical (thickness, solubility and permeability) and mechanic (tensile strength and elongation). Result of research show more chitosan add significantly increased thickness and tensile strength of edible film and significantly decrease solubility and elongation of edible film. But, edible film show no significantly decrease of permeability. Adding more chitosan in edible film starch-glycerol increase edible film thickness to 0,13 –1,90 mm and decrease solubility to 66,87–58,20%. Tensile strength show increase to 1,27–6,90 MPa and elongation decrease to 79,71–46,98%. And for permeability of edible film decrease to 12,40–9,97 (g/ hour m2).